2023
DOI: 10.1128/jvi.00099-23
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal Tropism of a Betacoronavirus ( Merbecovirus ) in Nathusius’s Pipistrelle Bat ( Pipistrellus nathusii ), Its Natural Host

Abstract: Virtually all mammal species circulate coronaviruses. Most of these viruses will infect one host species; however, coronaviruses are known to include species that can infect multiple hosts, for example the well-known virus that caused a pandemic, SARS-CoV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 58 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Recently, two novel bat merbecoviruses with complete genome sequenced, MOW-15-22 and PN-βCoV (designated PnNL2018B in this study), were independently reported by research teams in Russia and Netherlands 35,36 (Fig. 1a).…”
Section: Phylogenetic and Structural Analyses Suggest Ace2 Usage By M...mentioning
confidence: 84%
See 3 more Smart Citations
“…Recently, two novel bat merbecoviruses with complete genome sequenced, MOW-15-22 and PN-βCoV (designated PnNL2018B in this study), were independently reported by research teams in Russia and Netherlands 35,36 (Fig. 1a).…”
Section: Phylogenetic and Structural Analyses Suggest Ace2 Usage By M...mentioning
confidence: 84%
“…Nonetheless, the receptors for many merbecoviruses, including hedgehog coronaviruses (EriCoVs) such as HKU31, as well as several other bat coronaviruses like HKU5, MOW-15-22, and PN-βCoV remain elusive 29,[34][35][36] . Previous studies have suggested that HKU5 and HKU31 may not use DPP4 or ACE2 as their receptors, leaving their entry receptor identities to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MERS-CoV infection has resulted in approximately 2700 fatalities and sustained low-level local transmission in Saudi Arabia ( WHO, 2012 ). Relatives of MERS-CoV have been found in several animal species, including bats, camels, hedgehogs and pangolins ( Chen et al., 2023 ; Chu et al., 2014 ; Hemida et al., 2014 ; Lau et al., 2019 ; Luo et al., 2018 ; Mols et al., 2023 ; Shishido & Letizia, 2015 ; Speranskaya et al., 2023 ). Dromedary camels have been well-documented as intermediate hosts of MERS-CoV, and subsequent research has uncovered many relatives of MERS-CoV in bats, supporting the hypothesis that the origins and evolution of MERS-CoV trace back to bats ( Anthony et al., 2017 ; Chu et al., 2014 ; Cui et al., 2019 ; Lau et al., 2013 ; Memish et al., 2013 ).…”
mentioning
confidence: 99%